Novelty-induced phase-locked firing to slow gamma oscillations in the hippocampus : requirement of synaptic plasticity - Kitanishi, Takuma (2015)
Temporally precise neuronal firing phase-locked to gamma oscillations is thought to mediate the dynamic interaction of neuronal populations, which is essential for information processing underlying higher-order functions such as learning and memory. However, the cellular mechanisms determining phase locking remain unclear. By devising a virus-mediated approach to perform multi-tetrode recording from genetically manipulated neurons, we demonstrated that synaptic plasticity dependent on the GluR1 subunit of AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazole propionate) receptor mediates two dynamic changes in neuronal firing in the hippocampal CA1 area during novel experiences: the establishment of phase-locked firing to slow gamma oscillations and the rapid formation of the spatial firing pattern of place cells. The results suggest a series of events potentially underlying the acquisition of new spatial information: slow gamma oscillations, originating from the CA3 area, induce the two GluR1-dependent changes of CA1 neuronal firing, which in turn determine information flow in the hippocampal-entorhinal system.